Analysis of the Financial Performance of the Largest Consumer Goods Company in Indonesia Before and During the Covid-19 Pandemic (Case Study at PT. Unilever Indonesia Tbk) - Sukma Annisa Suwadji; Sri Suryaningsum; Noto Pamungkas (Journal of International Conference Proceedings, 2021)
This research is case study research at PT. Unilever Indonesia. PT. Unilever Indonesia Tbk is the largest consumer goods company in Indonesia. The novelty of this research is original research, there has never been a case study of financial performance analysis using net profit data for the 2018 to 2021 quarter/interim reports. This research is important to do because of the phenomenon of the COVID-19 pandemic condition in consumer goods companies. This is important considering that in 2020 the COVID-19 pandemic resulted in many sectors being affected by this pandemic, including the Consumer Goods sector. The purpose of this paper is to examine an in-depth analysis of the financial performance of PT. Unilever Indonesia Tbk. The analysis was carried out by comparing the condition of financial performance before and after the Covid-19 condition, with the mean difference analysis technique. Data testing was carried out for the mean conditions of Q1, Q2, Q3 2018 and 2019 before the Covid-19 pandemic with a mean of Q1, Q2, Q3 2020 and 2021 during the Covid-19 pandemic. The hypothesis proposed is that the condition of financial performance conditions before and during the Covid-19 pandemic. The results of this research found that there was no significant difference between the financial performance of PT. Unilever Indonesia Tbk. previous to a pandemic and during the event of pandemic covid-19.